Airway Administration of Bacterial Lysate OM-85 Protects Mice Against Respiratory Syncytial Virus Infection - Antunes, Krist Helen; Cassão, Gisele; Santos, Leonardo Duarte; Borges, Sofia Giacomet; Poppe, Juliana; Gonçalves, João Budelon; Nunes, Eduarda da Silva; Recacho, Guilherme Fernando; Sousa, Vitória Barbosa; Da Silva, Gabriela Souza; Mansur, Daniel; Stein, Renato T.; et al. (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) is a seasonal pathogen responsible for the highest percentage of viral bronchiolitis in pediatric patients. There are currently no vaccine available and therapeutic methods to mitigate the severity of RSV bronchiolitis are limited. OM-85, an oral standardized bacterial lysate isolated from human respiratory strains and widely used to prevent recurrent infections and/or exacerbations in populations at risk, has been shown to be effective and safe in children and adults. Here, we demonstrate that airway administration of OM-85 in Balb/c mice prior to infection prevents RSV-induced disease, resulting in inhibition of viral replication associated with less perivascular and peribronchial inflammation in the lungs. These protective effects are dose and time-dependent with complete protection using 1mg dose of OM-85 only four times intranasally. Mechanistic insights using this topical route in the airways revealed increased alveolar macrophages, a selective set of tolerogenic DCs, Treg and Th1 expansion in the lung, even in the absence of infection, contributing to a better Th1/Th2 balance and preventing ILC2 recruitment in the airways and associated inflammatory sequelae. OM-85 preventive treatment also improved antiviral response by increasing IFNβ and its responsive genes in the lung. In vitro, OM-85 protects against RSV infection in a type I interferon pathway. Our animal model data suggest that intranasal use of OM-85 should be considered as a potential prophylactic product to prevent RSV bronchiolitis once human studies confirm these findings.